SIRT7-Induced PHF5A Decrotonylation Regulates Aging Progress Through Alternative Splicing-Mediated Downregulation of CDK2 - Yu, Ai Qing; Wang, Jie; Jiang, Shi Tao; Yuan, Li Qun; Ma, Hai Yan; Hu, Yi Min; Han, Xing Min; Tan, Li Ming; Wang, Zhi Xiao (Frontiers in Cell and Developmental Biology, 2021)
Dysregulation of protein posttranslational modification (PTM) can lead to a variety of pathological processes, such as abnormal sperm development, malignant tumorigenesis, depression, and aging process. SIRT7 is a NAD+-dependent protein deacetylase. Besides known deacetylation, SIRT7 may also have the capacity to remove other acylation. However, the roles of SIRT7-induced other deacylation in aging are still largely unknown. Here, we found that the expression of SIRT7 was significantly increased in senescent fibroblasts and aged tissues. Knockdown or overexpression of SIRT7 can inhibit or promote fibroblast senescence. Knockdown of SIRT7 led to increased pan-lysine crotonylation (Kcr) levels in senescent fibroblasts. Using modern mass spectrometry (MS) technology, we identified 5,149 Kcr sites across 1,541 proteins in senescent fibroblasts, and providing the largest crotonylome dataset to date in senescent cells. Specifically, among the identified proteins, we found SIRT7 decrotonylated PHF5A, an alternative splicing (AS) factor, at K25. Decrotonylation of PHF5A K25 contributed to decreased CDK2 expression by retained intron (RI)-induced abnormal AS, thereby accelerating fibroblast senescence, and supporting a key role of PHF5A K25 decrotonylation in aging. Collectively, our data revealed the molecular mechanism of SIRT7-induced k25 decrotonylation of PHF5A regulating aging and provide new ideas and molecular targets for drug intervention in cellular aging and the treatment of aging-related diseases, and indicating that protein crotonylation has important implications in the regulation of aging progress.